PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN BREBES - Sri Ratih Handayani; Jaka Waskito; Mr. Gunistiyo (Multiplier: Jurnal Magister Manajemen, 2018)
The purpose of this study was 1) To determine the effect of motivation and on employee performance at the Regional Representative Council Secretariat in Brebes Regency 2) To determine the effect of leadership on employee performance at the Regional Representative Council Secretariat Brebes 3) To determine the effect of motivation and leadership together the same to the performance of employees in the Secretariat of the People's Representative Council of Brebes. respondent from this study were 55 people. Data sources used were questionnaire, observation, interview and literature study. This research method is descriptive research with a quantitative approach, namely the data used in the form of numbers that are analyzed using statistics. Oriented research is more focused on matters relating to the influence of motivation and leadership on employee performance. The research object revolves around factors motivational factors that influence employee performance include physiological aspects, appreciation, security and self-actualization and leadership and employee performance. From the results of data analysis conducted, it can be concluded that there is a positive relationship of motivation (X1) to employee performance (Y). It can be seen in the results of multiple regression tests obtained regression coefficient 0.265 (X1), which indicates that every one percent increase in motivation will cause an increase employee performance is equal to the coefficient value. And there is a positive relationship between leadership (X2) on employee performance (Y) this can be seen in the results of multiple regression tests obtained regression coefficient 0.362 (X2), which shows that every one percent increase in leadership will cause an increase in employee performance at the coefficient value.Keyword: motivation, leadership, performance